Managing the different stages of unexpected events: an exploratory analysis of tourism family businesses - Pusceddu, Gianluca; Moi, Ludovica; Cabiddu, Francesca (Piccola Impresa / Small Business, 2023)
Purpose: This study aims to explore how family businesses (FBs) redesign their business strategies throughout the different stages of unexpected events. Design/methodology/approach: This article performs an exploratory multiple-case in the context of 10 Italian firms operating in the tourism sector. Findings: The study develops a circular event framework illustrating the key business strategies implemented by FBs in the different moments of unpredicted circumstances: (1) leverage digital tools to facilitate relationships with customers and ensure business operations, during the crisis prevention phase; (2) identify and meet customer protection and safety needs, and take care of customers human-ly, during the crisis response phase; (3) renew customer value creation, in the crisis recovery phase. Originality of the study: This study contributes to the extant literature on crisis management by identifying the main strategies developed by FBs to address customer relationships across the crisis prevention, response, and recovery phases. This work represents a robust benchmark for managers and practitioners to make more informed strategic and operational decisions, increasing their capacity to act when addressing the different moments of a crisis event.